RE-OS FRACTIONATION IN MAGMATIC SULFIDE MELT BY MONOSULFIDE SOLID SOLUTION - Brenan J.M. (My University, 2002)
In order to better evaluate the effect of monosulfide solid solution (MSS) crystallization on Re–Os fractionation in magmatic sulfide ore systems, MSS–sulfide melt partition coefficients for Re and Os have been measured in experiments in the Fe–Ni–Cu–S system at 1100°C. Samples were encapsulated in evacuated silica tubes, run for durations of 13.5–61 h, and the compositions of coexisting MSS–melt pairs were characterized by electron microprobe. Average MSS–sulfide melt partition coefficients for Re and Os are 2.5 and 3.8, respectively, and are independent of experiment duration and MSS metal/sulfur ratio. Comparison of DOs measured in this study with values determined by Fleet et al. [Contrib. Mineral. Petrol. 115 (1993) 36–44] also suggests DOs is constant for melt Os contents ranging from 0.2 to 2000 ppm. Combining these data with a simple model of closed-system MSS fractionation reveals that the Re and Os content of coexisting MSS–residual sulfide melt pairs decreases with increased differentiation (as gauged by melt or MSS Cu abundances), whereas Re/Os ratios increase. This model reproduces the overall Re–Os–Cu trends observed in the zoned massive sulfide ore bodies at Noril’sk (Russia), although in detail, modeled Re variation is better predicted than Os or Re/Os variation. This latter result could suggest that the variation in ore Os content is not completely controlled by primary magmatic processes. In general, such results lend further support for the role of in situ differentiation in producing zoned ore bodies, but they also allow a clearer distinction to be made between primary vs. post-solidification processes in affecting the Re–Os isotopic system in sulfide-saturated igneous rocks.